Lipoxygenase: An Emerging Target for Stroke Therapy - Leyen, Klaus van (CNS & Neurological Disorders - Drug Targets, 2013)
Neuroprotection as approach to stroke therapy has recently seen a revival of sorts, fueled in part by the continuing necessity to improve acute stroke care, and in part by the identification of novel drug targets. 12/15- Lipoxygenase (12/15-LOX), one of the key enzymes of the arachidonic acid cascade, contributes to both neuronal cell death and vascular injury. Inhibition of 12/15-LOX may thus provide multifactorial protection against ischemic injury. Targeting 12/15-LOX and related eicosanoid pathways is the subject of this brief review.
Keywords: eicosanoid